Establishing governance of collaborative knowledge management system in public sector organisations - Ali, Azlina; Nor, Rozi Nor Haizan; Abdullah, Rusli; Azmi Murad, Masrah Azrifah (2014)
Many organisations have established knowledge management system (KMS) to facilitate the systematic creation and sharing of their knowledge resources. With the emerging trends of “connectedness” and globalisation, collaboration amongst these organisations has become an integral part of knowledge management, as new technologies continue to arise. To ensure the success and standardisation of collaborative KMS amongst Malaysian government agencies, proper governance needs to be in place. The aim of this paper is to identify governance component for collaborative KMS (CKMS). Journal articles published within the period 1998-2013 were identified and analyzed. The articles were sourced mainly from Knowledge Management Research &Practice, Science Direct, Emerald, MIS Quarterly, as well as some other academic databases. Keywords used during the literature search are “governance”, “knowledge management system”, “collaboration”, “collaborative knowledge management system”, “knowledge sharing” and “knowledge management governance”. Based on this analysis, the conceptual model for governance of collaborative knowledge management system is constructed.